Development of Internal Quality Assurance System Model for Pesantren Using the 2020 Education Unit Accreditation Instrument - Lathifah, Zahra Khusnul; Setyaningsih, Sri; Wulandari, Dian (JURNAL AL-TANZIM, 2022)
This study aims to analyze and understand the Development of pesantren (Islamic Boarding School's) Internal Quality Assurance System (SPMI) Model Based on the Education Unit Accreditation Instrument (IASP) 2020. This study uses a Research and Development (R&D) approach. The data collection technique is done through interviews, observation and documentation. While the data analysis was carried out in a circular manner, starting from data collection, data reduction and drawing conclusions. The results show that pesantren Internal Quality Assurance System (SPMI) Model which refers to the Education Unit Accreditation Instrument (IASP) 2020 was developed with a quality scheme in four main areas:  firstly, the quality of graduates, secondly, the quality of the process, thirdly, the quality of minimum standard achievements, and fourthly, the quality of management. (Islamic boarding school management).